Validation of Novel Microsurgical Vessel Anastomosis Techniques: A Systematic Review - Sadigh, Yasmin; Mechri, Imen; Jain, Anamika; Gautam, Amata Thongphetsavong; Seh, Hadil; Volovici, Victor (Journal of Reconstructive Microsurgery, 2024)
Background Thorough validation of novel microsurgical techniques is deemed essential before their integration into clinical practice. To achieve proper validation, the design of randomized controlled trials (RCTs) should be undertaken, accompanied by the execution of comprehensive statistical analyses, including confounder adjustment and power analysis. This systematic review aims to provide an encompassing overview of the validation methodologies employed in microsurgical studies, with a specific focus on innovative vessel anastomosis techniques.Methods A literature search was conducted in PubMed for articles describing the validation of novel microsurgical vessel anastomosis techniques in animal or human subjects.Results The literature search yielded 6,658 articles. A total of 6,564 articles were excluded based on title and abstract. Ninety-four articles were assessed for full-text eligibility. Forty-eight articles were included in this systematic review. Out of 30 comparative studies, 9 studies validated novel modified interrupted suture techniques, 6 studies modified continuous techniques, 6 studies modified sleeve anastomosis techniques, 1 study a modified vesselotomy technique, 7 studies sutureless techniques, and 1 study a modified lymphaticovenular anastomosis technique. Twenty-eight studies contained animals (n = 1,998). Fifteen animal studies were RCTs. Two studies contained human/cadaveric subjects (n = 29). Statistical power analysis and confounder adjustment were performed in one animal study. Out of 18 noncomparative studies, 5 studies validated novel modified interrupted suture techniques, 1 study a modified continuous technique, 2 studies modified sleeve anastomosis techniques, 4 studies modified vesselotomy techniques, 4 studies sutureless techniques, and 2 studies modified lymphaticovenular anastomosis techniques. Ten studies contained animal subjects (n = 320), with two RCTs. Eight studies contained human subjects (n = 173). Statistical power analysis and confounder adjustment were performed in none of the animal or human studies.Conclusion The current methods of microsurgical technique validation should be reconsidered due to poor study design. Statistical analysis including confounder adjustment and power analysis should be performed as a standard method of novel technique validation.
Keywords: microsurgery; surgical technique; vessel anastomosis; validation